Development of Islamic microfinance: a sustainable poverty reduction approach. Issue 3 (2nd September 2019) - Begum, Halima; Alam, A.S.A. Ferdous; Mia, Md Aslam; Bhuiyan, Faruk; Ghani, Ahmad Bashawir Abdul
Abstract : Purpose: Though microfinance has been working for many years as a tool to eradicate poverty from its root, most of the least developed and developing countries are yet to significantly alleviate it from the society. The purpose of this paper is to focus on Shariah -based microfinance products in the context of sustainable poverty alleviation approach and provide them financial benefits to enhance their livelihoods. Design/methodology/approach: Here, this qualitative study critically analyzes the basics of the sustainable Islamic microfinance to exterminate the level of poverty. Findings: Islamic microfinance is a more ethical practice than the traditional motives of profit maximization, and it encourages extending the time of repayment if the debtors are in hardship. In some case, it suggests to give charity if the creditor has capability. Research limitations/implications: Most importantly, research scholars and experts have already criticized the concept of conventional microfinance on the basis of various points, especially for its high rate of interest. Social implications: Islamic microfinance is provided with a view to fulfill two tools simultaneously, i.e., social and financial inclusion. In this case, credits and Zakah can be given to the extreme poor people for satisfying basic needs. In terms of social responsibility, Islam encourages the people to be soft in case of collecting the lending money. Originality/value: The study discoursed that sustainable Islamic Microfinance (IM) may be a promising future option to draw the attention of the religiously sensitive people toward the Shariah -based microfinance which can, in turn, mitigate the poverty level.